OP80 Formative evaluation of the UK NHS diabetes prevention programme demonstrator phase: review of baseline information. (13th September 2016) - Rodrigues, AM; Sherrington, A; Penn, L; Bell, R; Summerbell, CD; White, M; Adamson, AJ; Sniehotta, FF
Abstract : Background: The NHS diabetes prevention programme (NHS DPP) aims to identify people at high-risk of developing Type 2 diabetes, and offer them an intensive lifestyle change intervention (ILCI). The development, evaluation and implementation of the NHS DPP is planned in phases, starting with formative evaluation of a demonstrator phase. This study aims to 1) review and appraise activities related to recruitment, intervention delivery and equality across the seven NHS DPP demonstrator sites; and 2) inform the further development and ability to evaluate the programme. Methods: Information from documentation supplied by demonstrator sites was extracted and mapped against recommendations contained in NICE guidance PH38 (prevention of diabetes), NHS DPP specification and equality indicators. To facilitate the mapping exercise, themes within the guidance documents were identified and used in a coding framework to characterise demonstrator site programmes. Mapping was conducted by three reviewers and discrepancies were resolved through discussion. Results: Elements identified were categorised within four themes: (a) raising awareness and recruitment; (b) intervention components, design and delivery; (c) inequalities and adaptation and; (d) quality assurance, monitoring and training. Responsibilities for awareness raising and enrolment in the ILCI were unclear. In all sites referral to ILCI was via primary care or NHS Health Checks. Where a blood test was reported HbA1c was the most usual measure. Intervention content reporting was insufficiently detailed and varied across sites. The proposed programmes were less intensive and shorter than recommended. Place of residence and gender impacted on ILCI delivery in terms of choice of venue and availability of single-sex groups. Recommended minimum data items to evaluate programmes (age, sex, ethnicity, postcode, height, weight, HbA1c and physical activity levels) were specified by five sites, whereas dietary data were only specified by one site. Programme deliverers included a range of professionals. The training received varied across sites, with regular review of intervention delivery, the deliverer and their training needs in some sites. Conclusion: This review developed a useful framework to reflect on the different elements, actors and responsibilities needed to implement an evaluable NHS DPP. Information provided at baseline from some sites, had items missing from intervention content, equality indicators and quality assurance procedures. Findings were used to make recommendations for the subsequent stages of the NHS DPP implementation and evaluation. Lack of clarity and detail in intervention specification will jeopardise evaluability of the NHS DPP.